The Effects of Resisted Post-Activation Sprint Performance Enhancement in Elite Female Sprinters - Matusiński, Aleksander; Pietraszewski, Przemysław; Krzysztofik, Michał; Gołaś, Artur (Frontiers in Physiology, 2021)
Considering the effectiveness of resisted sprint training, and the acute enhancement of sprinting performance through locomotor post-activation performance enhancement, the main objective of the research was to determine the acute effects of resisted activation with loads of 5, 10, and 15% body mass on sprint and flying start sprint performance in elite female sprinters using resisted drag technology system. Ten elite female sprinters (age: 23.2 ± 5.4 years, body mass: 54.2 ± 6.1 kg, height: 167.4 ± 7.3 cm, personal best for 100 m: 12.05 ± 0.56 s, and for 400 m: 53.17 ± 2.76 s) performed two unresisted 20-m sprints (from a crouched and flying start) before and after a single resisted sprint loaded with 5, 10, or 15% body mass to verify the effectiveness of the activation stimulus. Compared with pre-activation, Friedman tests showed that peak velocity increased by 1.6 ± 2.2% [effect size (ES) = 0.66], 2.3 ± 1.5% (ES = 1.33), and 0.2 ± 1% (ES = 0.09), as well as peak force by 2.8 ± 2.1% (ES = 0.49), 3.5 ± 2.3% (ES = 1), and 0.5 ± 2.4% (ES = 0.14), concomitant with a significant decreased in sprint time by −0.5 ± 1.2% (ES = −0.07), −2.5 ± 1.3% (ES = −0.64), and −1 ± 1.4% (ES = −0.36) for the 5, 10, and 15% body mass post-activation, respectively (p < 0.001; for all). Furthermore, the ANOVA showed that peak power increased by 2.9 ± 2.3% (ES = 0.61), 3.8 ± 2.2% (ES = 1.05), and 2 ± 7.1% (ES = 0.22) for the 5, 10, and 15% body mass resisted-conditioning activity, respectively, with no difference between the three conditions (p = 0.003 main effect time, no interaction). Moreover, compared with the 5 and 15% body mass trials [−1.5 ± 2% (ES = −0.44), −0.8 ± 0.8% (ES = −0.44), respectively], the ANOVA showed that flying start sprint time significantly decreased by −4.3 ± 1.1% (ES = −1.25) (p < 0.001, interaction effect) after a 10% body mass resisted-conditioning activity. The results of this study indicated that resisted sprints acutely enhance sprint performance; however, their effectiveness depends on the applied load. A single resisted sprint using 10% body mass is effective at inducing a potentiating effect on subsequent 20-m flying start sprint performance in elite female sprinters. Therefore, keeping in mind the optimal load, it is recommended to perform resisted sprints as a conditioning activation when seeking to acutely enhance 20-m flying start sprint performance in these athletes.